Samisk tradisjonell kunnskap og utdanning for bærekraftig utvikling - Kvivesen, Mona (Cappelen Damm Akademisk, 2023)
Students should learn about the Sami people’s traditional knowledge and approach to nature in science education. Science teachers, therefore, must become proficient in Sami culture and traditions. Sami traditional practitioners have expertise, and it is important to bring out their voices. In this case study, six reindeer owners are interviewed, and the results show that the siida welcomes student participation in reindeer herding as a means of enabling students to learn about Sami culture and language. Sami traditional knowledge is strongly linked to nature and can help to strengthen students’ connection to nature. Strong connections to natureincrease environmental awareness and can contribute to students making more sustainable choices. Learning about Sami traditional knowledge together with Sami reindeer herders in nature as a learning arena embraces several elements in education for sustainable development and is a context that lends itself well to socio-scientific issues as education for sustainable development.